Assessment and validation of on-package handling and cooking instructions for raw, breaded poultry products to promote consumer practices that reduce the risk of foodborne illness - DeDonder, Sarah Elizabeth (Kansas State University, 2012)
Not-ready-to-eat entrées purchased at retail and prepared in the home have been identified as a risk factor for salmonellosis. From 1998 to 2010, ten outbreaks implicated undercooked not-ready-to-eat entrées. In each outbreak, affected individuals prepared entrées in a microwave oven, did not follow recommended cooking instructions, and failed to take the internal temperature of the cooked product. This dissertation surveyed grocery stores for product availability, evaluated consumers’ preparation practices of raw, breaded, frozen chicken entrées, and validated on-package label instructions. The survey of retail revealed that several manufacturers fail to provide consumers clear preparation instructions. A video capture system was used to observe food preparation practices of 41 consumers–21 primary meal preparers and 20 adolescents–in a mock domestic kitchen using uncooked, frozen, breaded chicken products, and determined if differences exist between consumers’ reported safe food handling practices and actual food handling behavior as prescribed on product labels. Differences between self-report and observed food safety behaviors were identified between groups. Many participants reported owning a food thermometer (73 percent) and reported using one when cooking raw, breaded chicken entrées (19.5 percent); however, only five participants (12.2 percent) were observed measuring the final internal temperature with a food thermometer despite instructions on the product packaging to do so. Food handling errors identified during the meal preparation sessions were then mimicked in a controlled laboratory setting to determine the impact of such deviations on end-product temperature. For all products, highly variable internal temperatures were recorded across entrées when prepared in a 600W microwave oven. Microwave cooking of raw breaded poultry products is unpredictable in achieving uniform target end-point temperatures; however, a 1000W microwave oven consistently produced a safe end product. Data collected through direct observation more accurately reflected consumer food handling behaviors than data collected through self-reported surveys. Low wattage microwave ovens failed to produce a safe end product. Processors should validate instructions for not-ready-eat entrées using a range of microwave ovens rather than a single wattage, develop a unique set of instructions for entrées, and provide consumers clear cooking instructions that result in a safe end product.
Keywords: Not-ready-to-eat entrees; Direct observation; Self-report survey; Microwave cooking instructions; Food safety; Food Science (0359)